The capacity to consent to sex in mental health inpatient units. (November 2019) - Maylea, Christopher
Objective: Discussions of capacity to consent in mental health care usually revolve around capacity to consent to treatment. This paper instead explores the issue of capacity to consent to sexual activity in a mental health inpatient setting as a way of exploring capacity from a different perspective. This is not a purely theoretical exercise, with both consensual sexual activity and sexual assault commonplace in mental health inpatient units, current policy and practice approaches are clearly not working and require re-examination. Methods: Four key frameworks are explored: human rights law, mental health law, the criminal law and the law of tort governing the duty of care. These frameworks are explored by highlighting relevant case law and statutes and considering their potential application in practice. This is undertaken using the state of Victoria, Australia, as a case study. Results: The four frameworks are shown to be consistent with each other but inconsistent with contemporary policy. All four legal frameworks explored require clinicians to take a case-by-case assessment to ensure that a person's right to make their own decisions is preserved ' unless the contrary is demonstrably justified ' or where it is ' legally demanded '. While Victorian inpatient units attempt to enforce a blanket ban on consensual sexual activity in inpatient settings, this ban may be without legal basis and may be in breach of both human rights and mental health law. Conclusion: In policing the lawful bodily interactions of their patients and pushing sexual activity out of sight, clinicians may be breaching their duty of care to provide sexual health support and risk creating an environment in which the therapeutic relationship will be sacrificed to the enforcement of institutional policy. Clinicians and policymakers must understand the relevant legal frameworks to ensure that they are acting ethically and lawfully.